Perancangan Logo SEE SYSTEM Untuk Membangun Brand Awareness Sebagai Aplikasi Online Untuk Prospecting Databse Customer - Jusuf Fadilah; Teguh Tri Susanto; Eddy Kusnadi (Universitas Bina Sarana Informatika, 2018)
Abstract - Each dealer has its own way to monitor the activities or prospects of each customer, the process of recording prospect activity is still using a conventional system where the method of recording is done manually, therefore made an online application to upload an online consumer database that can be accessed by all dealer salespeople. Each application must have its own icon or logo, the logo comes from the word logos which in Greek means word, thought, speech, reason. The use of the logo can be done anywhere, one of them is the logo on the SEE SYSTEM application, SEE SYSTEM application is newly created and has never had a logo before, the purpose of this research is SEE SYSTEM logo design to build awareness as an online application for prospecting database customer activities as well to analyze the philosophical meaning of the SEE SYSTEM logo. Keywords: Dealer, Logo, SEE SYSTEM